2007
DOI: 10.1111/j.1464-410x.2007.07188.x
|View full text |Cite
|
Sign up to set email alerts
|

Frozen section‐guided wide local excision in the treatment of penoscrotal extramammary Paget’s disease

Abstract: OBJECTIVE To analyse the clinicopathological characteristics of penoscrotal extramammary Paget’s disease (EMPD) and to discuss the outcomes after frozen section‐guided wide local excision. PATIENTS AND METHODS From 1990 to 2005, at our institution, 38 patients with penoscrotal EMPD received wide local excision with intraoperative frozen‐section analysis. Their medical records were reviewed for patient demographics, lesion characteristics, surgical margin status, and clinical outcome. RESULTS No patients had EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 25 publications
1
42
1
Order By: Relevance
“…A median surveillance period of 24 months is not very long, but we can cautiously state that wide local resection probably provides a cure in individuals with superfi cial penoscrotal EMPD according to our previous research [ 2 ] . Conversely, if deep invasion of tumours into subcutaneous tissues is suspected intraoperatively, this method should be reserved with caution not only for the sake of oncological control, but also because aggressive resection can damage the underlying blood supply for future grafts (especially for the distal skin of the penis).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…A median surveillance period of 24 months is not very long, but we can cautiously state that wide local resection probably provides a cure in individuals with superfi cial penoscrotal EMPD according to our previous research [ 2 ] . Conversely, if deep invasion of tumours into subcutaneous tissues is suspected intraoperatively, this method should be reserved with caution not only for the sake of oncological control, but also because aggressive resection can damage the underlying blood supply for future grafts (especially for the distal skin of the penis).…”
Section: Discussionmentioning
confidence: 88%
“…Early studies by our research team indicated that frozen section-guided wide local resection produces an acceptable prevalence of recurrence (16%) when treating penoscrotal EMPD. In general, the prognosis for primary penoscrotal EMPD confi ned to the epidermis is excellent [ 2 ] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8] However, local wide excision and immediate reconstruction is the preferred treatment of Chinese urologists. [9][10][11] Our experience with 130 patients evaluated at mid-term follow-up demonstrated that intraoperative frozen-section biopsy was a reliable means to detect invisible tumours and could significantly reduce recurrence. 3 When we used this technique to completely resect the lesions and preserve normal tissues, we encountered the challenge of reconstructing the different sizes and shapes of postoperative skin defects ( Figures 1b, 2b, 3b and 4b).…”
Section: Introductionmentioning
confidence: 99%